2020
DOI: 10.1038/s41598-020-73158-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of protocadherin-15 with the scaffold protein whirlin supports its anchoring of hair-bundle lateral links in cochlear hair cells

Abstract: The hair bundle of cochlear hair cells is the site of auditory mechanoelectrical transduction. It is formed by three rows of stiff microvilli-like protrusions of graduated heights, the short, middle-sized, and tall stereocilia. In developing and mature sensory hair cells, stereocilia are connected to each other by various types of fibrous links. Two unconventional cadherins, protocadherin-15 (PCDH15) and cadherin-23 (CDH23), form the tip-links, whose tension gates the hair cell mechanoelectrical transduction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…PCDH15 assembles in the membrane together with lipoma HMGIC Fusion Partner-Like 5 (LHFPL5,TMHS) (Ge et al, 2018, p. 5) and pull-down studies using protein fragments suggest that PCDH15 may also interact with TMC-1 (Maeda et al, 2014). PCDH15 is also theorized to interact with the cytoskeleton via whirlin (Michel et al, 2020), while TMC may be coupled to the cytoskeleton via CIB2 and ankyrin repeats (Tang et al, 2020). However, the molecular composition of the MT machinery and the 3D arrangements of each component remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PCDH15 assembles in the membrane together with lipoma HMGIC Fusion Partner-Like 5 (LHFPL5,TMHS) (Ge et al, 2018, p. 5) and pull-down studies using protein fragments suggest that PCDH15 may also interact with TMC-1 (Maeda et al, 2014). PCDH15 is also theorized to interact with the cytoskeleton via whirlin (Michel et al, 2020), while TMC may be coupled to the cytoskeleton via CIB2 and ankyrin repeats (Tang et al, 2020). However, the molecular composition of the MT machinery and the 3D arrangements of each component remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In harmonin, this extension folds as a hairpin followed by a short α-helix mediating the formation of a heterotopic supramodule between the first PDZ and the upstream Harmonin Homology Domain (HHD) and forming direct contacts with residues upstream of the partner’s PBM ( Yan et al, 2010 ) (PDB entry 3k1r). This supramodule displays ∼10 fold increased affinity for protocadherin-15 compared to the isolated PDZ ( Michel et al, 2020 ). In whirlin, the first and second PDZ domains interact via their respective C-terminal extensions, structured as hairpins, promoting the formation of a homotypic supramodule that improves the binding capacity of the PDZ tandem by ∼3 fold ( Delhommel et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…All three main PCDH15isoforms; PCDH15-CD1, -CD2, and -CD3, which differ in their cytoplasmic domain (Fig. 1b), are expressed in the hair cell bundle 25,27 . We obtained or cloned murine full-length (FL) and generated cytoplasmic (cyto) domain cDNA constructs for all three isoforms.…”
Section: Generation and Validation Of Pcdh15 Constructs And Antibodiesmentioning
confidence: 99%
“…Hair cells express three isoforms of PCDH15 (PCDH15-CD1, -CD2, and -CD3) that share a common extracellular domain but differ in the C-terminal region of their cytoplasmic tails 25 . The expression levels, localization, and role of each isoform is not fully understood but several studies have shown partial redundancy within the three PCDH15 isoforms during development with the CD2 isoform being essential for proper MET function in mature auditory hair cells [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%